Helicopter Parenting and the Moderating Impact of Gender and Single-Parent Family Structure on Self-Efficacy and Well-Being. (July 2020) - Buchanan, Tom; LeMoyne, Terri
The intersection of helicopter parenting, gender, and single-parent family on self-efficacy and well-being is examined. Existing research on helicopter parenting focuses on negative consequences. Using a sample of students at a university in the mid-southern United States ( N = 247), we find that helicopter parenting is negatively related to self-efficacy and well-being for emerging adult sons from single-parent family backgrounds. Previous research suggests a negative relationship of divorce on sons. In addition, our study finds no substantive relationship of helicopter parenting to self-efficacy and well-being for women. This is an intriguing finding given previous research finding negative consequences. The impacts of helicopter parenting are not uniform across different demographic groups. This information is important for family counselors as well as university administrators in relation to the growing concern for parental involvement in students' affairs.